PERANCANGAN SISTEM AKUNTANSI PENGGAJIAN PADA PT. MAAN GHODAQO SHIDDIQ LESTARI JOMBANG - Fauziatun Nisa'; Dianita Meirini (ITB AAS Indonesia Surakarta, 2023)
One of the determining factors in the performance of a company as a means to achieve company goals is human resources. Therefore, good human resources have the right to get a salary according to their quality. An effective payroll system will affect employee satisfaction at work and will undoubtedly affect their performance. This study aims to determine the implementation of the company's payroll accounting system and to find out how the implementation of the payroll accounting system design can be implemented in the company. The object of this research is the payroll system at PT. Maan Ghodaqo Shiddiq Lestari. The data analysis technique used in this study is case study analysis which aims to understand the organization in depth to help the organization achieve better adjustments so that weaknesses are found. Then based on this analysis, a payroll accounting system design is created that can help overcome weaknesses. Based on this analysis, there are several areas for improvement, including multiple positions in each section. With the creation of the payroll accounting system that has been made, it is hoped that it will help overcome the weaknesses that occur in payroll activities at PT. Maan Ghodaqo